Investigating the reading skill challenges of the first-year non-major students of English - Dương, Thị Huyền (University of Languages and International Studies, 2017)
With an investigation of challeges to reading skills at Hatay Community College, the purpose of the current study was to uncover challenges to such reading sub-skills as reading for specific information, finding the main ideas, guessing vocabulary from the context, making inferences.